Construction of genetic linkage map in tartary buckwheat (Fagopyrum tataricum) using SSR - Du X; Zhang, Z.; Wu B.; Li Y; Yu AH (2013)
The present study was aimed to construct a molecular linkage map of tartary buckwheat, which would provide essential tools for investigating genomic structure and evolution, and facilitate QTL mapping, marker-assisted selection and map-based cloning of important gene. In this study, a population of F4 generation including 119 individual plants was derived from the cross between ‘Dianning 1’ and a tartary buckwheat wild species. SSR markers were used to construct the molecular genetic linkage map. The genetic linkage map consisted 15 linkage groups with 89 markers including 22 (24.7%) distorted markers in the whole map and 2-16 markers in each linkage group. The total length of the map was 860.2 cM. The length of linkage groups varied from 6.9 to 165.8 cM, with a mean marker interval distance of 9.7 cM between markers. The current study constructed a first tartary buckwheat genetic linkage map, which provided the basis for the research on gene location and molecular breeding of tartary buckwheat.